Understanding telephone electronics - Bigelow, Stephen J. (Newnes, 2001)
Throughout its history, Understanding Telephone Electronics has been, by far, one of the most popular books on telecommunication electronics in the trade, electronic distribution, and educational markets because of its very simple, direct approach to the technology. In keeping with the distinguished tradition of its predecessors, Understanding Telephone Electronics, Fourth Edition covers conventional telephone fundamentals, including both analog and modern digital communication techniques, and provides basic information on the functions of each telephone system component, how electronic circuits generate dial tones, and how the latest digital transmission techniques work. This new edition of Stephen Bigelow's well-known, widely used text on telephone electronics offers comprehensive coverage of the latest developments in fiber optic technology, the convergence of telecommunications, cable-TV and Internet services, and CTI (computer telephony integration). The authors have made extensive revisions in these and other essential areas, such as business systems, voice mail, phone networking, enhanced services, satellite communications, wireless paging systems, digital communications, and much more to ensure that topics covered are current with the most recent advances in technology. The original Understanding Telephone Electronics has been a "gold standard" reference and training staple for years. Likewise, Understanding Telephone Electronics, Fourth Edition will serve as an essential and invaluable resource for technicians, engineers, students at major universities and corporations, and anyone with an enthusiasm for telecommunication electronics. Provides comprehensive coverage of telephone system functions and the role of the Internet in telephony Updates encompass the trends and advances of the booming telecommunications field, with new chapters on fiber optic technology and the Internet.